Eksistensi Teknologi dalam Pendidikan Agama Islam - Fadlil Khalis; Unik Hanifah Salsabila; Kamala Sukma Juliyanti; Dyah Ayu Putri Utami; Iffatur Rohmah (Peneliti.net, 2023)
AbstractEducation is a process of conveying knowledge that is conveyed by educators to students, but more than that education is expected to be able to bring about changes in student behavior in a better direction. Learning Islamic Religious Education aims to improve the morals of students based on the Al-Qur'an and As-Sunnah. Over time, the learning process applied has changed with the times by using various educational technologies. Islamic Religious Education teachers are expected to be able to change learning methods to be more effective. With better technological media, it is hoped that it will be able to improve learning. The method in this study uses the literature study method, namely by collecting information data sources that are relevant in the preparation of this research. Keywords: education, Islamic religious education, educational technology